Opinions of Scholars in the Era of Dahir Rulings of "Evacuation" in Islamic Jurisprudence - A., P. Sukaina Hussein Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
The rulings of Evacuation (discharging excrement out of the body) are considered as important ritual rules in the Islamic Jurisprudence. This is because they contain many Islamic legal issues that have a direct relation between the Creator and His servants concerning the authenticity (validity) of worship.